Representatividad de la composición de tallas del gatuzo Mustelus schmitti (Chondrichthyes, Triakidae) capturado por la flota artesanal y de arrastre comercial en la costa atlántica uruguaya - Pereyra, Inés; Paesch, Laura; Norbis, Walter (Revista de Biología Marina y Oceanografía, 2022)
The determination of the optimal sample size is important to obtain an adequate estimation of the size frequency distribution, as well as consistent estimators of the population parameters corresponding to the size composition, such as the mean value. In this work, the optimal sample size was determined to obtain a consistent estimate of the mean and a representative length frequencies distribution for Mustelus schmitti caught by artisanal and industrial fisheries off the Uruguayan coast. With representative samples, the mean estimators, its confidence interval, and the median with the 25 and 75% quartiles could be used to analyze temporal trends related to changes in the size structure.